Hydraulic polymer cement composition and method for application thereof
Patent Information
- Application Number
- JP2020178577
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-10-26
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2040-10-26
AI Technical Summary
【0015】 本発明の水硬性ポリマーセメント組成物は、床下地コンクリート表面に2.5mm~9mmに塗付することができる効果があり、また、硬化した塗膜の内部に発生する応力である収縮応力が極めて小さいという効果がある。このため、直接床下地コンクリート上に上記厚み塗付しても硬化後の塗膜が剥離することがないという効果がある。
Smart Images

Figure 0007609602000003 
Figure 0007609602000004 
Figure 0007609602000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a mortar-like hydraulic polymer cement composition which comprises at least a water-dispersible polyol, a polyisocyanate, an organometallic catalyst, a hydraulic cement, and an aggregate and is applied to a floor base concrete surface to a depth of 2.5 mm or more and less than 10.0 mm, and to a method for applying the same. [Background technology]
[0002] Conventionally, mortar-like hydraulic polymer cement compositions applied to the surface of a floor base concrete have a coating film with extremely large shrinkage force, and therefore easily peel off when simply applied to the surface of the floor base concrete. Therefore, as shown in claim 3 of Patent Document 1, it was necessary to first remove the fragile layer of the floor base concrete, create grooves 7 to 13 mm deep and 7 to 13 mm wide at the edges of the floor base concrete, and if the distance between opposing grooves exceeds 12 m, create joints 7 to 13 mm deep and 7 to 13 mm wide at intervals within 12 m from the grooves, and then apply the composition directly onto the floor base concrete to a thickness of 6 to 9 mm while filling the grooves and joints.
[0003] To solve this problem, Patent Document 2 proposes a composition that is designed to reduce the shrinkage force of the coating film by blending a specific diluent into the composition, allowing it to be applied without creating grooves or joints 7 to 13 mm deep and 7 to 13 mm wide in the floor base concrete.
[0004] In addition, Patent Document 3 proposes a hydraulic polymer cement composition as a mortar-like hydraulic polymer cement composition containing a water-dispersible polyol, a polyisocyanate, cement, aggregate, and water, which is applied to the surface of a concrete substrate in a thickness of 3 mm to 5 mm.
[0005] Furthermore, Patent Document 4 proposes a paste-like hydraulic polymer cement composition that is applied to the surface of a floor base concrete to a depth of 0.2 mm or more and less than 4.0 mm, and a method for applying the composition. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2015-81325 A [Patent Document 2] JP 2016-17024 A [Patent Document 3] JP 2017-65942 A [Patent Document 4] JP 2020-37508 A
[0007] However, even though the composition described in Patent Document 2 can suppress the shrinkage force to a low level, as shown in the examples, even if crude MDI (4,4'-diphenylmethane diisocyanate) is used in the polyisocyanate, which is expected to increase the coating strength, the compressive strength is approximately 21 N / mm 2 However, there is an issue that it does not have sufficient performance for use in, for example, food factory floors, which require higher strength and resistance to thermal shock and impact.
[0008] In addition, the hydraulic polymer cement composition of Patent Document 3, as shown in the examples thereof, uses crude MDI (4,4'-diphenylmethane diisocyanate, polymethylpolyphenyl polyisocyanate) as the polyisocyanate, as in the above, and the compressive strength is 31.0 N / mm 2 However, the composition has a high shrinkage rate of the coating film, and as shown in the evaluation method for thermal shock resistance in paragraph 0036 of the same patent document 3, it is necessary to provide joints 10 mm deep and 10 mm wide 5 mm inside from the ends of the four sides of the test specimen. In other words, if the test specimen does not have such joints, there is a problem that the coating film will easily peel off due to the shrinkage force when evaluating thermal shock resistance.
[0009] Furthermore, when polymethylpolyphenylpolyisocyanate is used as the polyisocyanate in the compositions of Patent Documents 2 and 3, there is a problem that the composition yellows significantly when exposed to ultraviolet light, and the color of the composition applied to the floor changes, eventually turning brown and impairing the aesthetic appearance.
[0010] Furthermore, the composition of Patent Document 4 has the problem that fine cracks may occur on the coating surface over time. Summary of the Invention [Problem to be solved by the invention]
[0011] The problem that the present invention aims to solve is to provide a hydraulic polymer cement composition and an application method thereof, which is a mortar-like hydraulic polymer cement composition to be applied to the surface of a floor base concrete to a thickness of 2.5 mm to 9.0 mm, and yet has a coating film with a small shrinkage stress so that the coating film will not peel off even when applied directly to the surface of the floor base concrete, and therefore does not require the provision of grooves with a depth of 7 to 13 mm and a width of 7 to 13 mm at the edges of the floor base concrete or joints with a depth of 7 to 13 mm and a width of 7 to 13 mm at intervals of up to 12 m from the grooves. Furthermore, despite the small shrinkage stress of the coating film, the composition has high compressive strength, impact resistance and thermal shock resistance, and furthermore, does not change color due to ultraviolet light, and in addition, does not cause fine cracks to occur on the coating film surface over time, and is also aesthetically pleasing. [Means for solving the problem]
[0012] In order to solve the above problems, the invention described in claim 1 is a hydraulic polymer cement composition comprising a water-dispersible polyol, a polyisocyanate, an organometallic catalyst, glycerin, a hydraulic cement, and an aggregate, the water-dispersible polyol contains water, a castor oil-based trifunctional polyol, and a tetrafunctional polyol having a bisphenol A skeleton, has a hydroxyl equivalent of 500 to 800, and is 4 to 10 parts by weight per 100 parts by weight of the entire composition; the castor oil-based trifunctional polyol is more than 30 parts by weight and not more than 50 parts by weight based on 100 parts by weight of the water-dispersible polyol; The amount of glycerin is more than 0 parts by weight and not more than 5 parts by weight per 100 parts by weight of the total composition, The polyisocyanate is an aliphatic isocyanurate, and the polyisocyanate is 5 to 15 parts by weight based on 100 parts by weight of the entire composition; The hydraulic cement is 5 to 15 parts by weight based on 100 parts by weight of the total composition. The aggregate is 70 to 85 parts by weight per 100 parts by weight of the total composition. The present invention provides a hydraulic polymer cement composition comprising:
[0013] The invention according to claim 2 provides the hydraulic polymer cement composition according to claim 1 or 2, characterized in that the polyisocyanate is hexamethylene diisocyanurate.
[0014] The invention described in claim 3 provides a method for applying the hydraulic polymer cement composition described in claim 1 or 2 to a surface of floor base concrete in a thickness of 2.5 to 10 mm. Effect of the Invention
[0015] The hydraulic polymer cement composition of the present invention has the effect of being able to be applied to the surface of floor base concrete to a thickness of 2.5 mm to 9 mm, and also has the effect of causing extremely small shrinkage stress, which is the stress generated inside the hardened coating film, so that even if the composition is applied directly to the floor base concrete to the above thickness, the hardened coating film will not peel off.
[0016] In addition, since the hydraulic polymer cement composition of the present invention has an extremely small shrinkage stress of the coating film as described above, there is an effect that it is not necessary to provide joints of 7 to 13 mm in depth and 7 to 13 mm in width at the edge of the floor base concrete or every 12 m or less on the floor base concrete surface as in the past. Therefore, there is an effect that it can be applied to the floor base concrete surface easily and in a short time, and as a result, there is an effect that it is low cost.
[0017] In addition, the hydraulic polymer cement composition of the present invention has an effect of having sufficient compressive strength, impact resistance, and thermal shock resistance, even though the shrinkage stress generated inside the coating film is extremely small. Of course, even when a special characteristic such as thermal shock resistance is not required, the hydraulic polymer cement composition of the present invention can be used.
[0018] In addition, since the hydraulic polymer cement composition of the present invention contains an aliphatic isocyanurate as the polyisocyanate, the coating film after curing does not yellow due to sunlight or ultraviolet rays, etc., and has an excellent appearance.
[0019] In addition, the hydraulic polymer cement composition of the present invention has good application workability even when applied to a thickness of 2.5 to 5 mm, which is slightly thinner than conventional compositions, and has sufficient thermal shock resistance to prevent peeling, cracking, etc., even when washed with hot water, as is done on food factory floors.
[0020] Furthermore, the hydraulic polymer cement composition of the present invention has the effect that after it is applied to the surface of a floor base concrete and hardens, there is almost no generation of fine cracks on the coating surface over time. [Brief description of the drawings]
[0021] [Figure 1] This is a model diagram of coating film peeling, viewed from the cross-sectional direction of the coating film, showing the state in which the coating film of a coating floor material applied to the surface of a base concrete material peels off at an angle of 5 degrees due to the coating film shrinkage force T. [Diagram 2]FIG. 1 is a graph showing the relationship between the surface tensile strength and the residual laitance rate of a base concrete with a water-cement ratio of 60%. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] The present invention will be described in detail below.
[0023] The hydraulic polymer cement composition of the present invention, in the case of the hydraulic polymer cement composition of claim 1, is a hydraulic polymer cement composition comprising a water-dispersible polyol, a polyisocyanate, an organometallic catalyst, glycerin, a hydraulic cement, and an aggregate, in which the water-dispersible polyol contains water, a castor oil-based trifunctional polyol, and a tetrafunctional polyol having a bisphenol A skeleton, the hydroxyl equivalent is 500 to 800, and is 4 to 10 parts by weight in 100 parts by weight of the entire composition, and the castor oil-based trifunctional polyol is 4 to 10 parts by weight in 100 parts by weight of the water-dispersible polyol. the amount of glycerin is more than 0 part by weight and not more than 5 parts by weight per 100 parts by weight of the total composition; the polyisocyanate is an aliphatic isocyanurate, the amount of polyisocyanate is 5 to 15 parts by weight per 100 parts by weight of the total composition; the amount of hydraulic cement is 5 to 15 parts by weight per 100 parts by weight of the total composition; and the amount of aggregate is 70 to 85 parts by weight per 100 parts by weight of the total composition. In addition to these, additives such as pigments, dispersants, antifoaming agents, diluents, etc. can be blended as necessary.
[0024] The water-dispersible polyol used in the present invention contains water, a castor oil-based trifunctional polyol, and a tetrafunctional polyol having a bisphenol A skeleton, and the castor oil-based trifunctional polyol is castor oil and its derivatives, such as diglycerides and monoglycerides of castor oil fatty acids and mixtures thereof, and is a polyol having three hydroxyl groups. systemThe hydroxyl equivalent of the trifunctional polyol is preferably 250 to 450, and if it is less than 250, the shrinkage stress of the cured product becomes large, causing the coating film to peel off from the underlying concrete, or the curing becomes too fast, resulting in poor workability, and if it exceeds 450, the strength after curing as a hydraulic polymer cement composition becomes insufficient. The content of the castor oil-based trifunctional polyol in the water-dispersible polyol is preferably more than 30 parts by weight and not more than 50 parts by weight in 100 parts by weight of the water-dispersible polyol, and if it is 30 parts by weight or less, the compressive strength may be insufficient, and if it exceeds 50 parts by weight, the thermal shock resistance may be insufficient.
[0025] The tetrafunctional polyol having a bisphenol A skeleton is an epoxy ring-opening polyol obtained by reacting a polyepoxy compound having a bisphenol A skeleton with an active hydrogen compound, and the hydroxyl equivalent is preferably 250 to 450. If the hydroxyl equivalent is less than 250, the shrinkage stress of the cured product increases, causing the coating film to peel off from the base concrete, or the curing speed increases, resulting in poor workability, and if it exceeds 450, the strength after curing as a hydraulic polymer cement composition is insufficient. The content of the tetrafunctional polyol having a bisphenol A skeleton in the water-dispersible polyol is preferably more than 2 parts by weight and not more than 15 parts by weight in 100 parts by weight of the water-dispersible polyol, and if it is 2 parts by weight or less, the compressive strength may be insufficient, and if it exceeds 15 parts by weight, the thermal shock resistance may be insufficient.
[0026] The hydroxyl equivalent of the water-dispersible polyol used in the present invention is preferably 500 to 800, and if it is less than 500, the hydraulic polymer cement composition will harden too quickly, resulting in poor workability, and if it exceeds 800, the hydraulic polymer cement composition will have insufficient strength after hardening. The amount of the water-dispersible polyol blended is preferably 4 to 10 parts by weight per 100 parts by weight of the total composition, and if it is less than 4 parts by weight, the strength of the hardened product of the composition will decrease, and if it exceeds 10 parts by weight, the workability when applying the composition with a metal trowel will decrease.
[0027] The amount of glycerin used in the present invention is more than 0 parts by weight and not more than 5 parts by weight per 100 parts by weight of the total composition, and is an amount that restores the compressive strength, impact resistance, and thermal shock resistance that become insufficient due to the addition of the above-mentioned tetrafunctional polyol having a bisphenol A skeleton.
[0028] The polyisocyanate used in the present invention is obtained from an aliphatic polyisocyanate and is composed of an aliphatic isocyanurate having an isocyanurate structure. More specifically, hexamethylene diisocyanurate obtained by cyclotrimerizing 1,6-hexamethylene diisocyanate is preferred because it has excellent weather resistance and improves the hardness of the coating film. The method described in JP-A-01-33115 can be used to cyclotrimerize 1,6-hexamethylene diisocyanate, and the polyisocyanate used in the present invention can be used in combination with other aliphatic diisocyanates, alicyclic diisocyanates, etc., or prepolymers thereof, and a polyisocyanate content of 99% by weight or more is used.
[0029] The polyisocyanate used in the present invention may have an NCO% of 15 to 25% by weight, and more preferably has an NCO% of 20 to 25% by weight. If it is less than 15% by weight, the strength of the coating film may be insufficient, and if it exceeds 25% by weight, the amount of polyisocyanate having an isocyanurate structure decreases, and conversely, the amount of polyisocyanate that is not trimerized, such as diisocyanate, increases, which also results in insufficient strength of the coating film.
[0030] In addition, the viscosity of the polyisocyanate used in the present invention is preferably 500 to 3500 mPa·s / 25°C. If it is less than 500 mPa·s, the strength of the coating film may be insufficient, while if it exceeds 3500 mPa·s, the workability when applying it to the base concrete surface may decrease.
[0031] The polyisocyanate used in the present invention is 5 to 15 parts by weight per 100 parts by weight of the total composition. If it is less than 5 parts by weight, the strength of the coating film may be insufficient, and if it exceeds 15 parts by weight, the curing time may be too short, resulting in insufficient workability.
[0032] The organometallic catalyst used in the present invention is blended to promote the curing of the present composition, and can be, for example, organometallic catalysts such as tin octylate, tin oleate, tin laurate, dibutyltin diacetate, dibutyltin diacetylacetonate, dibutyltin dilaurate, dibutyltin dichloride, lead octylate, lead naphthenate, and bismuth octylate. Among these curing catalysts, organotin compounds are more preferred. Among these curing catalysts, dibutyltin diacetylacetonate, dibutyltin diacetate, dibutyltin dilaurate, and dibutyltin dichloride are more preferred from the viewpoint of catalytic effect. The blending amount of the organometallic catalyst is 0.001 to 0.01 parts by weight in 100 parts by weight of the total composition. If it is less than 0.001 parts by weight, the strength of the coating film may be insufficient, and if it exceeds 0.01 parts by weight, the curing may be accelerated, resulting in poor application workability with a metal trowel or the like.
[0033] The hydraulic cement used in the present invention is preferably mainly white Portland cement so as to impart a specific color tone, and may also be used in combination with ordinary Portland cement, alumina cement, blast furnace cement, high-early-strength Portland cement, etc. The amount of hydraulic cement to be blended is preferably 5 to 15 parts by weight per 100 parts by weight of the total composition, with less than 5 parts by weight decreasing the strength of the coating film, and more than 15 parts by weight decreasing the workability of applying the composition to the base concrete surface with a metal trowel or the like.
[0034] The aggregates used in the hydraulic polymer cement composition of the present invention are a combination of a powdered insulator with a particle size of 1.0-3.0 mm, a silica sand with a particle size of 0.6-2.36 mm, a silica sand with a particle size of 0.21-1.18 mm, a silica sand with a particle size of 0.15-0.85 mm, a silica sand with a particle size of 0.05-0.6 mm, and a silica sand with a particle size of 0.04-0.3 mm. The powdered insulator is made by crushing insulators that are broken or discarded at an insulator production factory, and has the effect of imparting strength, abrasion resistance, heat resistance, etc. of ceramics to the floor. If the particle size is less than 1.0 mm, the workability of applying to the floor base concrete is poor, and if it exceeds 3.0 mm, the dispersibility in the composition and the unevenness of the coating surface after hardening become too large.
[0035] Silica sand with a particle size of 0.6 to 2.36 mm corresponds to silica sand No. 3, silica sand with a particle size of 0.21 to 1.18 mm corresponds to silica sand No. 4, silica sand with a particle size of 0.15 to 0.85 mm corresponds to silica sand No. 5, silica sand with a particle size of 0.05 to 0.6 mm corresponds to silica sand No. 6, and silica sand with a particle size of 0.04 to 0.3 mm corresponds to silica sand No. 7. For example, the combined ratio of insulator powder with a particle size of 1.0 to 3.0 mm, silica sand with a particle size of 0.21 to 1.18 mm, and silica sand with a particle size of 0.04 to 0.3 mm is preferably 8 to 12: 60 to 100: 0.5 to 2.0 by weight from the viewpoints of application workability, strength expression, impact resistance, etc. when applying to the floor base concrete at a thickness of about 5 to 9 mm. For example, the combined ratio of insulator powder having a particle size of 1.0 to 3.0 mm, silica sand having a particle size of 0.21 to 1.18 mm, and silica sand having a particle size of 0.05 to 0.6 mm is preferably 0.8-1.2:2.0-4.0:0.3-1.0 by weight from the viewpoints of application workability when applying the powder to a thickness of about 2.5 to 5 mm to the floor base concrete, strength development, impact resistance, and the like.
[0036] The amount of aggregate to be mixed is 70 to 85 parts by weight per 100 parts by weight of the total composition. If the amount is less than 70 parts by weight, the coating smoothness may be poor, and if it exceeds 85 parts by weight, the impact resistance may decrease.
[0037] In addition to the above, it is preferable to add slaked lime to the water-independent polymer cement composition of the present invention. The slaked lime absorbs carbon dioxide gas generated by the urea reaction between polyisocyanate and water, and has the effect of suppressing the concentration of carbon dioxide gas in specific areas, which pushes up the coating film and causes swelling, when the composition is applied to the floor base concrete and hardens.
[0038] The hydraulic polymer cement composition of the present invention is applied to the surface of the base concrete by applying it to a thickness of 2.5 to 9 mm using a metal trowel, wooden trowel, etc. Preferably, the composition is first spread and applied to the surface of the base concrete with a wooden trowel, and then the composition is applied to the surface of the base concrete to be worked on evenly to a predetermined thickness, while being firmly pressed down with a metal trowel as a finishing touch, so that it is integrated with the base concrete, thereby making it possible to obtain a coated floor with no defects in the hardened coating film and excellent appearance.
[0039] The present invention will be specifically described below with reference to examples and comparative examples. EXAMPLES
[0040] <Examples and Comparative Examples> As a water-dispersible polyol, castor oil with a hydroxyl equivalent of 350 systemThe mixture contains 35 to 40 parts by weight of trifunctional polyol, 5 to 10 parts by weight of tetrafunctional polyol having a bisphenol A skeleton with a hydroxyl equivalent of 360, 20 to 25 parts by weight of a sulfonic acid ester compound (Mezamol; product name, manufactured by Bayer) as a diluent, and 30 parts by weight of water (ion-exchanged water), totaling 100 parts by weight. The water-dispersible polyol A has a hydroxyl equivalent of 500 to 800, and the water-dispersible polyol B (water content: 200 to 2500 parts by weight) is made of a castor oil-based trifunctional polyol and has a hydroxyl equivalent of 280 to 560. and water-dispersible polyol C (water content: 25-30% by weight) containing 25-33 parts by weight of castor oil-based bifunctional polyol per 100 parts by weight of castor oil-based trifunctional polyol, with a hydroxyl equivalent of 200-250 overall, and water-dispersible polyol D (water content: 25-30% by weight) containing 14-20 parts by weight of castor oil-based bifunctional polyol per 100 parts by weight of castor oil-based trifunctional polyol, with a hydroxyl equivalent of 200-500 overall, and The polyisocyanate A was hexamethylene diisocyanurate (viscosity 2500 mPa·s / 25°C, NCO%: 20% by weight, polyisocyanate content 99% by weight or more) and the polyisocyanate B was 4,4´-diphenylmethane diisocyanate (NCO%: 31.0% by weight). The organometallic catalyst was Neostan U220H (dibutyltin diacetylacetonate). The aggregate was Celbene (trade name, company Using silica sand having a particle size of 0.21 to 1.18 mm: Tohoku Silica Sand No. 4 (trade name, manufactured by Tohoku Silica Sand Co., Ltd.), silica sand having a particle size of 0.05 to 0.6 mm: Tohoku Silica Sand No. 6 (trade name, manufactured by Tohoku Silica Sand Co., Ltd.), silica sand having a particle size of 0.04 to 0.3 mm: Tohoku Silica Sand No. 7 (trade name, manufactured by Tohoku Silica Sand Co., Ltd.), and white Portland cement (manufactured by Taiheiyo Cement Corporation) as hydraulic cement, hydraulic polymer cement compositions of the examples and comparative examples were prepared according to the blending ratios shown in Table 1. In the following evaluations, Example 1, Comparative Examples 1 to 3, Comparative Example 7, and Comparative Example 9 were evaluated after finishing to a coating thickness of 7 mm, and Example 2, Comparative Examples 4 to 6, Comparative Example 8, and Comparative Example 10 were evaluated after finishing to a coating thickness of 3 mm.
[0041] [Table 1]
[0042] <Evaluation items and evaluation methods>
[0043] <Paint finish> The hydraulic polymer cement compositions of the Examples and Comparative Examples were applied to a specified thickness with a metal trowel to the surface of a dried JISA5371 concrete slab measuring 300 mm x 300 mm x 60 mm thick (5% or less measured with a HI-520 concrete moisture meter in the concrete range) at 23°C, and the surface condition of the coating was visually observed. A smooth finish was rated as ◯, and an uneven finish was rated as ×.
[0044] <Impact resistance> The hydraulic polymer cement compositions of the Examples and Comparative Examples were applied to a specified thickness with a metal trowel onto the surface of a dried JISA5371 concrete slab (5% or less measured with a HI-520 concrete range moisture meter) at 23°C. After curing for 7 days, a 1 kg steel ball was dropped 60 times from a height of 1 m onto the center of the slab. Those without any abnormalities such as cracks or peeling were rated as ◯, and those with abnormalities such as cracks or peeling were rated as ×.
[0045] <Compressive strength> The hydraulic polymer cement compositions of the Examples and Comparative Examples were cured at 23°C for 7 days, and the compressive strength (N / mm 2 The size of the test specimen was 13mm x 13mm x 25mm. The compressive strength was 22N / mm 2 If it was more than this, it was deemed to have sufficient strength and was evaluated as ◯, and if it was less than this, it was evaluated as x.
[0046] <Thermal shock resistance and microcrack resistance> A dried concrete plate (JISA5371) measuring 300 mm x 300 mm x 60 mm thick (5% or less measured with a Kett moisture meter HI-520 concrete range) was cut into quarters to obtain a test plate measuring 150 mm x 150 mm x 60 mm thick. The surface of the test plate was thoroughly roughened with sandpaper #80 to remove the brittle layer, and the hydraulic polymer cement compositions of the Examples and Comparative Examples were mixed uniformly and applied to a thickness of 7 mm for the hydraulic polymer cement compositions of Example 1, Comparative Examples 1 to 3, Comparative Example 7, and Comparative Example 9, or to a thickness of 3 mm for the hydraulic polymer cement compositions of Example 2, Comparative Examples 4 to 6, Comparative Example 8, and Comparative Example 10, and allowed to cure for 7 days. After that, 95°C hot water was poured down the centre of the test piece for 5 minutes, followed by 20°C cold water for 10 minutes. This cycle was repeated 6,000 times for the 7mm thick test piece, and 4,000 times for the 3mm thick test piece. Those that did not experience any abnormalities such as peeling or lifting in the coating were rated as having good thermal shock resistance, those that did experience abnormalities were rated as having bad thermal shock resistance. Those that experienced fine cracks on the coating surface were rated as having bad microcrack resistance, and those that did not experience any microcracks were rated as having good microcrack resistance.
[0047] <Adhesion> The hydraulic polymer cement compositions of the Examples and Comparative Examples are applied to a surface of a dried JISA5371 concrete slab measuring 300 mm x 300 mm x 60 mm thick (5% or less measured with a HI-520 concrete range moisture meter) at 23°C with a metal trowel to a specified thickness. After curing for 7 days, the adhesion strength (N / mm ) between the 40 x 40 mm part of the hydraulic polymer cement composition and the concrete slab is measured using a Construction Research Institute type adhesion tester. 2 The state of failure was evaluated as ◯ when the concrete substrate had 100% cohesive failure, and as × otherwise.
[0048] <Peeling resistance> For the hydraulic polymer cement compositions of Example 1, Comparative Examples 1 to 3, Comparative Example 7, and Comparative Example 9, the hardened products were molded into strips measuring 160 mm in length, 10 mm in width, and 7 mm in thickness, and for the hydraulic polymer cement compositions of Example 2, Comparative Examples 4 to 6, Comparative Example 8, and Comparative Example 10, the hardened products were molded into strips measuring 160 mm in length, 10 mm in width, and 3 mm in thickness, and each was cured at 23°C for 7 days and then further heat cured at 50°C for 14 days to measure the shrinkage strain L (mm). Next, the specimen was pulled in the longitudinal direction at a speed of 1 mm / min, and the tensile elastic modulus E (N / mm 2 The shrinkage stress (N / mm2) per unit cross-sectional area of the coating film is calculated from the shrinkage strain L (mm) and the length L0 (mm) of the test specimen after aging at 23°C for 7 days using the following formula (1). 2 ) was calculated, and further, the coating film thickness was multiplied by 7 mm for Example 1, Comparative Examples 1 to 3, Comparative Example 7, and Comparative Example 9, and by 3 mm for Example 2, Comparative Examples 4 to 6, Comparative Example 8, and Comparative Example 10 to determine the coating film shrinkage force T (N / mm) per unit width of the coating film. Shrinkage stress (N / mm 2 ) = E(L / L0) (1) Here, the coating film shrinkage force T (N / mm) is empirically considered to act in a direction that causes the coating film to peel off. Therefore, based on model and experience, it is considered that the coating film shrinkage force at this time acts to pull the coating film at a shallow angle of about 5 degrees, causing the coating film to peel off, and was converted into the vertical force Tv (N / mm) per unit width (mm) of the coating film using the following formula (2). Vertical force Tv (N / mm) = sin5° × T (2) This normal force per unit width (1 mm) Tv (N / mm) is experimentally and empirically calculated as the normal force per unit width (1 mm) of the coating film, which is 7 mm or 3 mm thick, within 1 mm of the substrate to which the coating film is adhered. 2 The vertical force acts on the coating film relative to the unit surface area (1 mm 2 ) in the direction perpendicular to the load, and this is called the normal stress Tv2 (N / mm 2 ) was decided.
[0049] On that basis, first, Fig. 2 shows the relationship between the surface tensile strength and the residual laitance rate of the base concrete when the water / cement ratio is 60% (see Table 1 and Fig. 12 (air-dried state) in the Influence of Base Concrete on the Occurrence of Blisters in Painted Floors, Architectural Institute of Japan, Structural Engineering Journal, No. 493, 1-7, March 1997. Only the base cohesive failure is extracted from Fig. 12 (air-dried state) and shown in the figure), and the normal stress Tv2 (N / mm 2 ), and even if 100% of the laitance remained in the base concrete, the surface tensile strength of the base was 0.7N / mm 2 (Normally, the concrete base from which all laitance has been removed is suitable for application of floor coating materials.) 2 than normal stress Tv2 (N / mm 2 If the normal stress Tv2 (N / mm) is small, it is considered that the coating film will not peel off from the base concrete due to the action of the shrinkage force of the coating film alone, and it is rated as ⊚. 2 ) is the surface tensile strength of the base concrete of 0.7N / mm 2 When the laitance residual rate was greater than 100%, the coating film was rated as x since the coating film may destroy the surface of the underlying concrete and peel off due to the action of the shrinkage force of the coating film alone.
[0050] In addition, the 2012 edition of the Painted Floor Handbook (published March 1, 2012, supervised by Yu Yokoyama, edited by the Japan Painted Floor Industry Association, published and sold by Kobunsha) states that the surface (tensile) strength of newly constructed concrete and mortar that serve as the base for a painted floor and the quality of the renovated base is 1.5 N / mm 2 Therefore, this 1.5N / mm 2 and the normal stress Tv2 (N / mm 2 ) and the 1.5N / mm 2 than normal stress Tv2 (N / mm 2 If the normal stress Tv2 (N / mm) is small, it is considered that the coating film will not peel off from the base concrete due to the action of the shrinkage force of the coating film alone, and it is evaluated as ○. 2 ) has a surface (tensile) strength of 1.5N / mm 2When the shrinkage force was larger than the above value, the coating film was evaluated as x since the coating film may destroy the surface of the underlying concrete and peel off due to the action of the shrinkage force of the coating film alone.
[0051] Of the two above, at least the specified value of 1.5N / mm in the Floor Coating Handbook 2 If the judgement is ○, the peeling resistance is judged to be good, and if both are ×, it is judged that a groove 7 to 13 mm deep and 7 to 13 mm wide should be made at the edge of the floor base concrete, as in the conventional method, and if the distance between opposing grooves exceeds 12 m, joints 7 to 13 mm deep and 7 to 13 mm wide should be made every 12 m from the groove, and the composition should be filled into the grooves and joints and then applied onto the floor base concrete.
[0052] <Yellowing resistance> For the hydraulic polymer cement compositions of Example 1, Comparative Examples 1 to 3, 7, and 9, a 7 mm-thick cured coating film was applied, and for the hydraulic polymer cement compositions of Example 2, Comparative Examples 4 to 6, 8, and 10, a 3 mm-thick cured coating film was applied using a black light (germicidal lamp, peak wavelength 256 nm, 31 μW / cm 2 The color difference (ΔE) before and after irradiation was measured. ΔE of 1.0 or less was evaluated as ○, and ΔE of more than 1.0 was evaluated as ×.
[0053] <Evaluation Results> The evaluation results are shown in Table 2.
[0054] [Table 2]
Claims
1. A hydraulic polymer cement composition comprising a water-dispersible polyol, a polyisocyanate, an organometallic catalyst, glycerin, a hydraulic cement, and an aggregate, the water-dispersible polyol contains water, a castor oil-based trifunctional polyol, and a tetrafunctional polyol having a bisphenol A skeleton, has a hydroxyl equivalent of 500 to 800, and is 4 to 10 parts by weight per 100 parts by weight of the total composition; the castor oil-based trifunctional polyol is more than 30 parts by weight and not more than 50 parts by weight based on 100 parts by weight of the water-dispersible polyol, the content of the tetrafunctional polyol having a bisphenol A skeleton is more than 2 parts by weight and not more than 15 parts by weight based on 100 parts by weight of the water-dispersible polyol, The amount of the organometallic catalyst is 0.001 to 0.01 parts by weight based on 100 parts by weight of the total composition. The amount of glycerin is more than 0 parts by weight and not more than 5 parts by weight per 100 parts by weight of the total composition, The polyisocyanate is an aliphatic isocyanurate, and the polyisocyanate is 5 to 15 parts by weight per 100 parts by weight of the total composition; The hydraulic cement is 5 to 15 parts by weight based on 100 parts by weight of the total composition. The aggregate is 70 to 85 parts by weight per 100 parts by weight of the total composition. A hydraulic polymer cement composition comprising:
2. 2. The hydraulic polymer cement composition according to claim 1, wherein the polyisocyanate is hexamethylene diisocyanurate.
3. A method for applying the hydraulic polymer cement composition according to claim 1 or 2, which comprises applying the hydraulic polymer cement composition to a surface of a floor base concrete in a thickness of 2.5 to 10 mm.
Citation Information
Patent Citations
Strength improving agent for cement, aqueous solution of polycarboxylic acid-based copolymer, and cement composition
JP2006282414A
Method for producing cured article from hydraulic composition
JP2013006737A
Water-based polyurethane composition and construction method thereof to floor base concrete
JP2015081325A
Aqueous polyurethane composition and method for applying the same on floor substrate concrete
JP2016017024A
Hydraulic polymer cement composition
JP2017065942A